ENGAGING LEARNER PREFERENCES IN ONCOLOGY COMPETENCY VALIDATION THROUGH A DYNAMIC INTERACTIVE ONCOLOGY SKILLS DAY. - Fischer, Heidi; Apil, Anna Leah; Okrepka, Leia; Ross, Caroline; Drake, Kathleen (Oncology Nursing Forum, 2026)
Significance & Background: Oncology nurses are challenged with keeping abreast of advancements in cancer care. Inspiring and maintaining competence in performing all aspects of oncological care requires an adaptive environment adjusting to learner preferences. Novice oncology nurses participate in a structured orientation and initial competency validation. Experienced oncology nurses are required to complete an annual exam. Experienced oncology nurses expressed a desire to demonstrate annual competency in an innovative and dynamic interactive experience, as opposed to an annual exam. Purpose: The purpose of this evidence-based initiative is to create a dynamic learning experience and competency validation process aligning with learner preferences and inspires professional development from novice to expert. Interventions: A task force was created including the nurse educator and a team of oncology nurses who identified topics of interest from the Oncology Certification Blueprint. A focus on care continuum, survivorship, end-of-life issues, cancer basics, disease process, treatment modalities, symptom management, oncological emergencies, and psychosocial aspects were recognized as essential components for care of the oncology patient. Each topic was developed into interactive skills to validate competency. Learning strategies included gaming, role playing, problem-solving, simulation, and critical thinking activities. Logistical operations was coordinated by the nurse educator, securing room availability for two weeks. Collaboration with unit leadership commenced with scheduling nurses to rotate through the activity stations. The taskforce of experienced oncology nurses' competencies were validated by the clinical nurse educator. Then the taskforce received training to lead the skills stations and participated in the competency validation for the remaining participants. Participants were expected to demonstrate their knowledge, skill and attitude through all activity stations. Unsuccessful participants received remediation from the clinical nurse educator or an experienced oncology nurse and the participant was given an opportunity to demonstrate competency with an alternative activity. Results: The results are in progress. End of year competencies are due by December 2025. To date the team was established, activities created and competency validation approved by nursing leadership. Additional outcomes will include staff satisfaction and confidence, evidence of learning and increased engagement with the dynamic interactive competency skills stations. Discussion: Creating and supporting a culture of life-long learning is critical in developing and ensuring quality oncology care. Prioritizing innovative strategies for learning and competency validation strengthens nurse confidence and competence, creates an enjoyable work environment and values learner preferences.